Peran Strategi Pembelajaran Pendidikan Agama Islam dalam Membentuk Karakter Religius Peserta Didik di Era Society 5.0: The Role of Islamic Religious Education Learning Strategies in Shaping Students' Religious Character in the Era of Society 5.0 - Maulana Restu, Yanto; Mila Nurjamilah; Nafa Farhanah, Ai; Ali, Sayyidina; Hidayatuloh, Akil (CV. Kalimasada Group, 2024)
In the 5.0 era, where modern technology merges with human values, Islamic Education (PAI) is essential in developing the religious character of the younger generation. This article explores various effective teaching methods in PAI that focus on instilling strong religious values in students. By leveraging information and communication technology, including social media and educational apps, these approaches aim not only to deliver content but also to foster greater interaction and engagement among students in the learning process.Through the implementation of these methods, the goal is for students to evolve into individuals who are both intellectually adept and spiritually resilient. With a firm religious foundation, they are expected to tackle global challenges with confidence and integrity. The article stresses that effective PAI education should address the needs and expectations of today’s society, shaping a generation that is not only well-informed but also possesses a strong character and ethical values. Consequently, Islamic education in the 5.0 era has considerable potential to foster well-rounded individuals who are prepared to navigate the constantly changing dynamics of the world.